The effect of metabolic syndrome on postoperative complications and long-term survival of patients with colorectal cancer - Zhu, Ce; Mao, Chenchen; Cai, Wentao; Zheng, Jingwei; Yang, Hui; You, Tao; Chen, Jian; Yu, Yaojun; Shen, Xian; Li, Liyi (Frontiers in Oncology, 2023)
Abstract Background: Metabolic syndrome (MetS) is associated with poor prognosis in many cancers. However, the relationship between metabolic syndrome and overall survival (OS) in patients with colorectal cancer (CRC) remains unclear. We aimed to comprehensively analyze whether MetS could affect postoperative complications and long-term survival in patients with CRC. Methods: We included patients who underwent CRC resection at our center between January 2016 and December 2018. Bias was reduced through propensity score matching analysis. Patients with CRC were divided into the MetS and non-MetS groups based on whether they had MetS. Univariate and multivariate analyses were used to identify risk factors affecting OS. Results: We included 268 patients; among them, 120 were included for further analysis after propensity score matching. There were no significant between-group differences in the clinicopathological features after matching. Compared with the non-MetS group, the MetS group had a shorter OS (P = 0.027); however, there was no significant between-group difference in postoperative complications. Multivariate analysis revealed that MetS (hazard ratio [HR] = 1.997, P = 0.042), tumor-node-metastasis stage (HR = 2.422, P = 0.003), and intestinal obstruction (HR = 2.761, P = 0.010) were independent risk factors for OS. Conclusions: MetS affects the long-term survival of patients with CRC without affecting postoperative complications.